2009
DOI: 10.1007/s12206-009-0437-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response characteristics of seismic isolation systems for building structures

Abstract: Isolation is an effective method of reducing effects of seismic events on building structures. Steel-reinforced elastomeric isolator (SREI) is one kind of isolation system which is used extensively, but there are some problems associated with its use, such as cost and weight. Fiber-reinforced elastomeric isolator (FREI) has been developed in an attempt to solve the problems of high cost and heavy weight for SREI. In this study, mechanical properties for the SREI and the FREI are investigated. Systematic dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Similar trend of distribution of shear forces along the height of the considered buildings were also obtained by [46], and in experimental studies by [49,50]. The observed increase of shear forces as the building height increases has also been observed by other researchers [18], but for only one building height.…”
Section: Storey Shear Force and Storey Drift Profilessupporting
confidence: 87%
“…Similar trend of distribution of shear forces along the height of the considered buildings were also obtained by [46], and in experimental studies by [49,50]. The observed increase of shear forces as the building height increases has also been observed by other researchers [18], but for only one building height.…”
Section: Storey Shear Force and Storey Drift Profilessupporting
confidence: 87%
“…Recent analytical and experimental research studies show that properly designed seismic base isolation systems can reduce peak floor accelerations effectively. Kang et al (2009) have shown that seismic base isolation systems composed of steel-reinforced or fiber-reinforced elastomeric isolators reduce peak floor accelerations significantly. Ismail et al (2009b) have shown that the peak accelerations sustained by an equipment housed in the top story of an eight-story building model can effectively be reduced by seismically isolating the building via a rolling-based seismic isolation system.…”
Section: Seismic Isolation and The Distribution Of Floor Accelerationsmentioning
confidence: 99%
“…However, the distribution of peak floor accelerations of a seismically isolated building may be different due to the presence of the seismic isolation system. In the literature, only a limited number of studies on seismically isolated buildings considered all peak floor accelerations rather than only top floor accelerations (Nagarajaiah et al 1991a,b;Şahin 2008;Kang et al 2009;Providakis 2009). Reviewing these studies, we see a tendency in the floor accelerations to decrease towards mid-floors and then increase towards upper floors.…”
Section: Seismic Isolation and The Distribution Of Floor Accelerationsmentioning
confidence: 99%
“…As per the references, the first modern technique of base isolators was carried out in 1969 in a school building by using rubber isolators in Skopje, Macedonia [1,15]. But, in the last few decades, the base isolation concept has rapidly gained visibility across the globe, resulting in, development of various isolation systems [16]. In the current scenario, various base isolation devices are being used i.e.…”
Section: Introductionmentioning
confidence: 99%